FENOMENA IMPOSTOR SYNDROME PADA MAHASISWA BERPRESTASI (MAWAPRES) UNIVERSITAS ISLAM “45” BEKASI - Alfiana Indah Muslimah; Septia Catur Amalia; Alfiyah Nur Jauharah; Yunita Kurniawati; Alifah Qisthi Fadhiilah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2022)
Outstanding students are students who have succeeded in achieving high achievements, both curricular, co-curricular, and extra-curricular according to the specified criteria. However, the learning outcomes that lead to these achievements sometimes make some students feel that they do not deserve the award. In psychology, it is often referred to as the impostor phenomenon or known as the impostor syndrome. This qualitative study aims to determine whether or not there is an impostor syndrome phenomenon in outstanding students (MAWAPRES) at the Islamic University